Pemanfaatan Limbah Kulit Pisang dengan Tingkat Kematangan Berbeda Sebagai Pupuk Cair pada Pertumbuhan Tanaman Cabai Rawit (Capsicum frutescens L.) - Indar Dwi Musyadi; Zyahdatul Husna Herlianti; Lia Rismawati; Elis Kaiye; Maasje Catherine Watulingas (Politeknik Negeri Ketapang, 2025)
Banana peel waste is one of the organic materials that has high potential to be processed into liquid fertilizer because it contains macronutrients such as nitrogen (N), phosphorus (P), and potassium (K). This study aims to examine the effect of banana peel ripeness on the quality of liquid organic fertilizer (POC) produced and its effect on the growth of cayenne pepper plants (Capsicum frutescens L.). POC is made through fermentation of ripe and unripe banana peels with the addition of granulated sugar or EM4 for more than seven days. The parameters observed include plant height, number of leaves, and pH of the fertilizer solution. The results showed that the treatment of ripe banana peels with added sugar (P1) gave the best results, with plant height growth reaching 5.2 cm and the number of leaves as many as 5 strands on the 25th day. The increase in fertilizer pH from week 1 to 5 indicated the success of fermentation and transformation of organic compounds into inorganic ionic forms such as NO₃⁻, H₂PO₄⁻, and K⁺ which are easily absorbed by plants. This research proves that the principles of inorganic chemistry can be applied practically in the management of organic waste into effective and environmentally friendly liquid fertilizer.